2003
DOI: 10.1002/mus.10322
|View full text |Cite
|
Sign up to set email alerts
|

Congenital myopathies at their molecular dawning

Abstract: The introduction and application of molecular techniques have commenced to influence and alter the nosology of congenital myopathies. Long-known entities such as nemaline myopathies, core diseases, and desmin-related myopathies have now been found to be caused by unequivocal mutations. Several of these mutations and their genes have been identified by analyzing aggregates of proteins within muscle fibers as a morphological hallmark as in desminopathy and actinopathy, the latter a subtype among the nemaline myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 204 publications
(319 reference statements)
1
31
0
1
Order By: Relevance
“…Bars, 20 m. Quantification of desmin network organizations in transfected cells is shown in wild-type ␣B-crystallin (Selcen and Engel, 2003), again suggestive of a compromised protein degradation system. Indeed, the protein aggregates containing the desmin and ␣B-crystallin were not ubiquitin labeled (Selcen and Engel, 2003), which is unusual compared with other myopathies (Goebel and Warlo, 2000;Goebel, 2003). Satellite cells isolated from patients with the R120G ␣B-crystallin mutation were also more susceptible to oxidative stress (Nedellec et al, 2002) symptomatic of a compromised stress response.…”
Section: Late Onset Characteristic Of the Disease Linked To Specific mentioning
confidence: 94%
See 2 more Smart Citations
“…Bars, 20 m. Quantification of desmin network organizations in transfected cells is shown in wild-type ␣B-crystallin (Selcen and Engel, 2003), again suggestive of a compromised protein degradation system. Indeed, the protein aggregates containing the desmin and ␣B-crystallin were not ubiquitin labeled (Selcen and Engel, 2003), which is unusual compared with other myopathies (Goebel and Warlo, 2000;Goebel, 2003). Satellite cells isolated from patients with the R120G ␣B-crystallin mutation were also more susceptible to oxidative stress (Nedellec et al, 2002) symptomatic of a compromised stress response.…”
Section: Late Onset Characteristic Of the Disease Linked To Specific mentioning
confidence: 94%
“…DRMs caused by mutations in either the desmin or ␣B-crystallin gene are inherited neuromuscular disorders that are characterized by the accumulation of aggregates containing desmin and ␣B-crystallin (Vicart et al, 1998;Goebel and Warlo, 2001;Fischer et al, 2002;Goebel, 2003). Despite this direct physical association between desmin and ␣B-crystallin in patients with myopathy, analysis of the effects of R120G ␣B-crystallin in a mouse model (Wang et al, 2001) and a tissue culture model (Chavez Zobel et al, 2003) suggested that there was not a direct interaction between desmin and ␣B-crystallin.…”
Section: Aggregation Of Desmin Depends Upon Network Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Goebel e col. observaram um padrão autossômico dominante em quatro gerações sucessivas 4 , embora já tenham sido relatados casos esporádicos e de herança autossômi-ca recessiva em caso de pais consangüíneos 7,13 .…”
Section: Fig 1 Presença De Inclusões Citoplasmáticas Sugestivas De Cunclassified
“…MB subtype III was characterized by the absence of a well-deWned Wlamentous structure and the presence of highly electron dense granular or homogeneous inclusions, which resemble aggresomes (Johnston et al 1998;Garcia-Mata et al 1999;Kopito and Sitia 2000). Aggresomes are cytoplasmic inclusion bodies observed in several non-hepatic diseases such as in some myopathies (Goebel 2003), in Alexander disease (Hagemann et al 2006), and in neurodegenerative diseases including Alzheimer and Parkinson disease as well as in amyotrophic lateral sclerosis (Cairns et al 2004). They are formed when the proteolytic capacity of the proteasome is exhausted and misfolded proteins aggregate in the cytosol (Johnston et al 1998;Garcia-Mata et al 1999;Kopito and Sitia 2000).…”
Section: Introductionmentioning
confidence: 96%